2011
DOI: 10.4187/respcare.00999
|View full text |Cite
|
Sign up to set email alerts
|

Crackle Pitch and Rate Do Not Vary Significantly During a Single Automated-Auscultation Session in Patients With Pneumonia, Congestive Heart Failure, or Interstitial Pulmonary Fibrosis

Abstract: OBJECTIVE:To determine the variability of crackle pitch and crackle rate during a single automated-auscultation session with a computerized 16-channel lung-sound analyzer. METHODS: Forty-nine patients with pneumonia, 52 with congestive heart failure (CHF), and 18 with interstitial pulmonary fibrosis (IPF) performed breathing maneuvers in the following sequence: normal breathing, deep breathing, cough several times; deep breathing, vital-capacity maneuver, and deep breathing. From the auscultation recordings we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 23 publications
(26 reference statements)
0
11
0
Order By: Relevance
“…This has also been observed in subjects with interstitial pulmonary fibrosis when comparing crackle rate during normal and deep-breathing maneuvers. 37 This may be related to the effect of lung expansion, as recordings were repeated at short intervals. 38 During the first breathing maneuvers, regions of deflated airways probably opened, and in the following maneuvers, the production of crackles decreased.…”
Section: Discussionmentioning
confidence: 99%
“…This has also been observed in subjects with interstitial pulmonary fibrosis when comparing crackle rate during normal and deep-breathing maneuvers. 37 This may be related to the effect of lung expansion, as recordings were repeated at short intervals. 38 During the first breathing maneuvers, regions of deflated airways probably opened, and in the following maneuvers, the production of crackles decreased.…”
Section: Discussionmentioning
confidence: 99%
“…This method provides an estimate of gas flow. At the flow rates we used in this study, tracheal gas flow is proportional to the root mean square of the sound amplitude: doubling the gas flow results approximately in doubling the root mean square of the sound amplitude [4, 814]. …”
Section: Methodsmentioning
confidence: 99%
“…This suggests that mean nBC is a stable parameter that is not affected by airway clearance techniques, or that it is not responsive to change. Vyshedskiy et al 27 have recently reported on the stability of crackle rate within single examination sessions, despite intervening maximal breathing maneuvers. Recording for 25 second periods provided sufficient data for our crackle analysis.…”
Section: Discussionmentioning
confidence: 99%